(3GdJMaI GdHcQjI aj CMcGe GdCSJMeGe GdcdjI hGdLRFjIs - (3OGhO Hf YeQ GdHUjQ GdCfWGcj, J (B1008 (3g` s
(3ChdgG (B:s
(3jGef ZeS bdhH GdYGQajf ai HMGQ BdGFd hHYO adeG JVi GdUGOQ GdChd hCKHJ Pdc YJg s
(3BNQgG (B:s
(3hjSjQ ef GdRYaQGf , hjWjN MJi jfYbO , hHQaY s
(3QSGdI CTGQ Ydjg HJCdjagG TjN GdYGQajf eMeO GdHcQis
(3PcQ ajgG eHGMK Cgd GdUfGYIs
(3QJHgG Ydi ebOeI hSHY aUhds
(3hNGJeI s
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA GdWH (B- (3bSe GdcJGH GdcGed (B- (3U (B40 s
Keywords: (3GdWHs